Other Schistosomatoidea and Diplostomoidea - Horák, Petr; Bulantová, Jana; Mikeš, Libor (Advances in experimental medicine and biology, 2024)
Trematodes of the order Diplostomida are well known as serious pathogens of man, and both farm and wild animals; members of the genus Schistosoma (Schistosomatidae) are responsible for human schistosomosis (schistosomiasis) affecting more than 200 million people in tropical and subtropical countries, and infections of mammals and birds by animal schistosomes are of great veterinary importance. The order Diplostomida is also rich in species parasitizing other major taxa of vertebrates. The "Aporocotylidae" sensu lato are pathogenic in fish, "Spirorchiidae" sensu lato in reptiles. All these flukes have two-host life cycles, with asexually reproducing larvae usually in mollusks and occasionally in annelids, and adults usually live in the blood vessels of their vertebrate hosts. Pathology is frequently associated with inflammatory reactions to eggs trapped in various tissues/organs. On the other hand, the representatives of Diplostomidae and Strigeidae have three- or four-host life cycles in which vertebrates often serve not only as definitive but also as intermediate or paratenic hosts. Pathology is usually associated with migration of metacercariae and mesocercariae within the host tissues. The impact of these trematode infections on both farm and wild animals may be significant.
Keywords: Life Cycle Stages; stadia vývoje; infekce červy třídy Trematoda; Trematode Infections; Schistosomatidae; Animals; lidé; Host-Parasite Interactions; Humans; zvířata; interakce hostitele a parazita; Trematoda